STUDI EKSPERIMEN DAN ANALISA PERPINDAHAN PANAS KONVEKSI PADA SUATU RONGGA DENGAN VARIASI DERAJAT KEVAKUMAN - Mulyono Mulyono (Jurnal Gamma, 2006)
In the world of industry, isolation material is often used to maintain the substance temperature in thesituation cold or hot. Besides expensive and thick, the size usage of isolation material is sometimes lookedless practical. To replace the isolation material function is often air cavity by low pressure or vacuum.Making degree of vacuum exist 100 % at air cavity is not easy. Usually there is still air in cavity will cause thehappening of hot transfer of natural convection between both the surface of former cavity. Coefficient ofconvection hot transfer (h) at one cavity of besides influenced by different temperature it also influenced bycavity geometry, orient from cavity and characteristic that had by fluid, for example : pressure, temperature,specific mass, conductivities and viscosities.Problems that arising out in this research is how is the relation coefficient of convection hot transfer(h), number Nusselt (Nu), number of Rayleigh and resistance thermal (R) with the variation of degreevacuum exist at a cavity.Target of this research is to get the relation empirically of convection hot transfer coefficient (h),number Nusselt (Nu), number of Rayleigh and Resistance Thermal (R) with the existence of degree variationof vacuum exists at a cavity. While the benefit in this study is hamper the speed of hot transfer betweensystems with the media in around.